Frasa Verbal Bahasa Teon di Pulau Seram: Teon Language Verbal Phrases in Seram Island - Erniati, Erniati; Wijaya, Dendi (Kibas Cenderawasih, 2023)
This study aims to identify verbal phrases in the Teon language of Watludan Village, Seram Island, in Central Maluku District. Data collection was carried out using instruments containing Indonesian phrases which were then translated into Teon language phrases according to the data requirements. Data analysis was carried out by classifying all types of verbal phrases according to Teon language. After the data is classified, it is then analyzed based on the types of verval phrases by making formulas according to the phrase patterns of the Teon language. The results of the study show that the verbal phrases of Teon are divided into two, namely verbal phrases that can be divided into attributive endocentric verbal phrases and coordinative endocentric verbal phrases. Attributive endocentric verbal phrases consist of several types of phrases based on their attribute word classes, namely (1) verb phrases with the adverbial attribute of way, (2) verbal phrases with modal/aspect attributes, (3) verbal phrases with time averbial attributes, (4) verbal phrases with intensity attributes, (5) verbal phrases with negative attributes, (6) attribute verbal phrases in a negative way, (7) verbal phrases mean but adverbial ways; and (2) coordinate endocentric verbal phrases.